A quality indicator set for rehabilitation services for people with rheumatic and musculoskeletal diseases demonstrates adequate responsiveness in a pre-post evaluation - Anne-Len; Gunnhild Berdal; Maryam Azimi; Ingvild Bø; Turid Nygaard Dager; Siv Grødal Eppeland; Guro Ohldieck Fredheim; Anne Sirnes Hagland; Åse Klokkeide; Anita Dyb Linge; Kjetil Tennebø; Helene Lindtvedt Valaas; et al. (BMC, 2021)
Abstract Background Quality of care is gaining increasing attention in research, clinical practice, and health care planning. Methods for quality assessment and monitoring, such as quality indicators (QIs), are needed to ensure health services in line with norms and recommendations. The aim of this study was to assess the responsiveness of a newly developed QI set for rehabiliation for people with rheumatic and musculoskeletal diseases (RMDs). Methods We used two yes/no questionnaires to measure quality from both the provider and patient perspectives, scored in a range of 0-100% (best score, 100%). We collected QI data from a multicenter stepped-wedge cluster-randomized controlled trial (the BRIDGE trial) that compared traditional rehabilitation with a new BRIDGE program designed to improve quality and continuity in rehabilitation. Assessment of the responsiveness was performed as a pre-post evaluation: Providers at rehabilitation centers in Norway completed the center-reported QIs (n = 19 structure indicators) before (T1) and 6-8 weeks after (T2) adding the BRIDGE intervention. The patient-reported QIs comprised 14 process and outcomes indicators, measuring quality in health services from the patient perspective. Pre-intervention patient-reported data were collected from patients participating in the traditional program (T1), and post-intervention data were collected from patients participating in the BRIDGE program (T2). The patient groups were comparable. We used a construct approach, with a priori hypotheses regarding the expected direction and magnitude of PR changes between T1 and T2. For acceptable responsivess, at least 75% of the hypotheses needed to be confirmed. Results All eight participating centers and 82% of the patients (293/357) completed the QI questionnaires. Responsiveness was acceptable, with 44 of 53 hypotheses (83%) confirmed for single indicators and 3 of 4 hypotheses (75%) confirmed for the sum scores. Conclusion We found this QI set for rehabilitation to be responsive when applied in rehabilitation services for adults with various RMD conditions. We recommend this QI set as a timely method for establishing quality-of-rehabilitation benchmarks, promoting important progress toward high-quality rehabilitation, and tracking trends over time. Trial registration The study is part of the larger BRIDGE trial, registered at ClinicalTrials.gov (Identifier: NCT03102814).